Saint Lucia. Significant achievements 2019 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The main activities carried out by the Institute in Saint Lucia during 2019 are identified, with respect to the needs and interests of the country, strengthening issues of pest control, citrus disease (Huanglongbing), apiculture, resilience to change climate and agrotourism. Likewise, work was done on the development of the honey sector, on water storage, sanitation and food safety, the safe use of agrochemicals and the cocoa sector. Finally, it contributed to the development of agricultural trade and the use of electronic systems for phytosanitary certifications.